Building Knowledge Sharing: The Role of Empowering Leadership, Trust, and Organizational Commitment - , Noerchoidah; Harjanti, Dhyah; Fatimah, Nuzulul; Mahmudah, Siti; Widowati, Dyah (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to examine how to implement knowledge sharing by looking at empowering leadership, trust, and organizational commitment to private university lecturers in East Java. Design/methodology/approach: The type of research used is explanatory research, namely explaining the position of influence of the independent variables and dependent variables in the hypothesis. The population of this study were private university lecturers in East Java. Questionnaires were distributed online using purposive sampling techniques and 230 questionnaires were analyzed. Partial Least Square is used for data analysis. Research Findings: The results of the study reveal that empowering leadership and trust affects the success of knowledge sharing. In addition, organizational commitment has succeeded in mediating empowering leadership and trust which indirectly affects knowledge sharing. Theoretical Contribution/Originality: The practical implications can be used as consideration for the management of private universities in creating knowledge sharing for lecturers. Keywords: Empowering Leadership; Trust; Organizational Commitment; Knowledge Sharing